Double-Bundle Medial Patellofemoral Ligament Reconstruction With Allograft - Rosinski, Alexander (Arthrosc Tech, 2019)
Medial patellofemoral ligament (MPFL) reconstruction is the treatment of choice for recurrent patellofemoral instability. Although attention to MPFL reconstruction in the orthopaedic literature has increased dramatically in recent years, there is no clear consensus on surgical technique, graft option, or method of fixation. Nevertheless, most studies have shown improved pain scores and low rates of recurrent dislocation in patients after surgery. Despite the early success of MPFL reconstruction, complications may occur more frequently than previously appreciated and include patellar fracture, postoperative instability, and loss of flexion. This article describes our technique for double-bundle MPFL reconstruction with an allograft while highlighting certain aspects of the procedure that are critical for achieving favorable outcomes. The main advantages of the technique include strong patellar fixation with suture anchors and anatomic graft placement at the origin and insertion of the native MPFL. In our experience, this method of reconstruction has been safe, reproducible, and effective in the treatment of patients with patellar instability.